Exploring Project-Based Learning within an Independent Curriculum: A Qualitative Inquiry into Technical Drawing Competence in Vocational Automotive Education - Ridwan Ridwan; Riyan Saputra; Mardiyah Mardiyah (Journal of Transdisiplinary Studies in Education, 2025)
Background: Vocational education is undergoing curriculum reform that emphasizes learner autonomy and competency-based learning, yet evidence on its implementation in technical drawing instruction remains limited. Aims: This study examines the application of Project-Based Learning within the Independent Curriculum and its contribution to the development of technical drawing competence in vocational automotive education. Methods: This study employed a qualitative descriptive approach. Data were collected through classroom observations, learning document analysis, and reflective inputs from teachers and grade X students in an automotive vocational program. The analysis focused on instructional design, learning processes, assessment practices, and observed competency development. Result: The findings indicate that Project-Based Learning supports active engagement and contextual understanding in technical drawing instruction. Students demonstrated improved ability to interpret technical symbols, apply drawing standards, and relate drawings to automotive components. The learning process also encouraged collaboration and independent learning. Conclusion: Project-Based Learning is a suitable pedagogical approach for implementing the Independent Curriculum in vocational automotive education, as it strengthens technical drawing competence while promoting learner-centered learning practices.